150 Administration of prostaglandin F2α 24 h prior to CIDR removal impacts reproductive performance of suckled beef cows assigned to the 7-d CO-Synch + CIDR protocol. (29th July 2019) - Fontes, Pedro; Cooke, Reinaldo F; Oosthuizen, Nicola; Timlin, Claire L; Dias, Nicholas; Currin, John F; Clark, Sherrie; Lamb, Graham Cliff; Pohler, Ky G; Mercadante, Vitor R G
Abstract: Angus-influenced cows received 100 µg of GnRH and a CIDR device containing 1.38 g of progesterone (P4) on d 0, and were randomly assigned to 25-mg injection of PGF2α on d 6 (PG6; n = 147) or d 7 (PG7; n = 162). The CIDR device was removed on d 7, and cows received 100 µg of GnRH and artificial insemination (AI) on d 10. An estrus detection patch was attached to the tailhed of each cow on d 7, and estrus expression assessed at AI (> 50% coating removal). Blood samples were collected on d 0 to determine the presence of a functional corpus luteum via plasma P4 (CL, P4 ≥ 1.0 ng/mL; NOCL P4< 1.0 ng/ mL). A subset of cows (70 cows/treatment) were assigned to ultrasonography at AI to verify dominant follicle diameter (DFD). Blood samples for plasma P4 analysis were collected (42 cows/treatment) on d 6, and on d 7 at CIDR removal and 1 h later. A similar proportion of PG6 and PG7 cows were classified as CL (P = 0.38). Plasma P4 at CIDR removal and 1 h later were less in PG6 vs. PG7 cows classified as CL (1.81 vs. 3.99 and 1.06 vs. 2.89 ng/mL), and did not differ (P ≥ 0.43) within NOCL. Estrus expression was greater in PG6 vs. PG7 cows classified as CL (72.8 vs. 48.3%), but similar (P = 0.96) within NOCL. Pregnancy rates did not differ between treatments (P = 0.53), despite a numerical difference (P = 0.15) between PG6 vs. PG7 cows classified as CL (65.5 vs. 55.0%). No other treatment effects were detected (P ≥ 0.20). Hence, PGF2α administration 24 h prior to CIDR removal appears to benefit reproductive performance of beef cows with a functional CL at the beginning of the 7-d CO-Synch + CIDR protocol